Domestic Violence in Allende's Violeta - Vida Rahiminezhad; Haider Kadhim Jalil. AL-Mosawi (Critical Literary Studies)
Domestic is a term that encompasses intimate partner violence wherever it occurs and in whatever form. Galtung categorizes violence into three types of direct, structural, and cultural violence. The purpose of this article is to analyze Allende's Violeta (2022) based on Galtung's category of violence and Simeon de Beauvoir's feminist theory. This is a qualitative library-based study. Allende presents female characters who are victims of domestic violence at the hands of their husbands, their partners, and not their fathers. There are different types of domestic violence practiced against women and children in the novel due to the patriarchal perspective, culture, norms, and customs. Structural violence makes the role of cultural violence transparent. It is the role of cultural violence that legalizes structural violence. It is concluded that in order to eliminate domestic violence against women, the cultural violence resulting from the patriarchal system must be replaced with a new culture of anti-oppression, non-violence, and mutual understanding toward women.